Effect of Bed Preparation Methods on Yield, Yield Components, and Amount of Water Used in Three Varieties of Rice (Oryza sativa L.) in Isfahan Province - A. Ramazani; A. H. Jalali (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
To investigate the effect of three methods of bed preparation on yield, yield components, and amount of water used in three rice cultivars, a study was carried out in two regions, including Fozve Research Station (Isfahan Agricultural Research Center) and Zarinshahr, using a split plot experiment based on a complete block design in three replications in 2007. Three bed preparation methods (conventional, using roller and rotivator) were assigned as main factors and three rice genotypes (Sazandegi, Zayandehrud, and Line2) as sub-factors. The number of fertile tillers, plant height, panicle length, grain yield, yield components and percentage of hollow grains were measured. In Zarinshahr area, using rotivator led to higher grain yield in all the cultivars, compared to using roller and traditional methods. In this study, the highest grain yield (8700 Kg ha-1) was obtained using rotivator and the line2 cultivar in Zarinshahr area. The stem lodging extent in Zarinshahr, with the use of rollers in all cultivars, ranged from 15 to 25 percent, while the range for different cultivars, in conventional methods of bed preparation and use of rotivator was variable from 35 to 45 percent. The results of this study showed that although using both methods of rotivator and roller had higher yield than conventional methods of bed preparation, the use of roller, with lower water consumption per hectare in two regions of the Zarinshahr and Fozve, was proven more effective in reducing consumption of water per hectare. Based on the amount of water consumed, the use of roller and rotivator for bed preparation seems superior to the conventional method.